Truth Degrees Theory and Approximate Reasoning in 3-Valued Propositional Pre-Rough Logic - Yingcang Ma; Juanjuan Zhang; Huan Liu (Journal of Applied Mathematics)
By means of the function induced by a logical formula A, the concept of truth degree of the logical formula A is introduced in the 3-valued pre-rough logic in this paper. Moreover, similarity degrees among formulas are proposed and a pseudometric is defined on the set of formulas, and hence a possible framework suitable for developing approximate reasoning theory in 3-value logic pre-rough logic is established.